(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT: Indonesia is a country rich in natural resources, the natural resources that Indonesia has the capital to promote development and the country’s economy, but the extent to which it is known that the Indonesian people are less able to use these natural resources, especially people who lack the ability, as there is in the countryside very need direction or assistance from the government in managing natural resources more effectively. Based on the Human Rights Act Article 28c explains that every person has the right to develop themselves through the fulfillment of basic needs, is entitled to education and to benefit from science and technology, arts and culture, in order to enhance the quality of life and for the welfare of mankind. With the role of government is being implemented in accordance with the rules villages minister in 2015 and other laws, to direct, inform and even provide facilities for the farming community or rather empowering the livelihoods of the development will be better than ever. In the present study used qualitative data analysis method. Informants in this study was taken from the village where the government carry out the role and rural communities where the feel of the role. From the research that has been conducted shows that the government’s role in empowering rural farming community in the village of Boyong Pante has not been implemented properly because of the lack of ability of village government in directing the villagers, as well as the lack of compatibility between the villagers with the village government. Kaywords: village government, empowerment farmer